2011
DOI: 10.1007/s10008-011-1558-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different soft chemical routes synthesis of submicro-LiMn2O4 and their influence on its electrochemical properties

Abstract: A comparative study of submicro-crystalline spinel LiMn 2 O 4 powders prepared by two different soft chemical routes such as hydrothermal and sol-gel methods is made. The dependence of the physicochemical properties of the spinel LiMn 2 O 4 powder has been extensively investigated by using X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, cyclic voltammogram, charge-discharge test, and electrochemical impedance spectroscopy (EIS). The results show that the electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Lithium ion batteries, with their high energy density, long cycle life, lack of a memory effect, low self-discharge rate, environmental friendliness and many other advantages, have become the primary choice of energy storage device in portable electronics, and have been intensively investigated for use in high power applications. 1,2 LiMn 2 O 4 is typically obtained by the reaction of a mixture of lithium salt (e.g. CH 3 COOLi$2H 2 O) and manganese oxides at around 750 C in air for many hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium ion batteries, with their high energy density, long cycle life, lack of a memory effect, low self-discharge rate, environmental friendliness and many other advantages, have become the primary choice of energy storage device in portable electronics, and have been intensively investigated for use in high power applications. 1,2 LiMn 2 O 4 is typically obtained by the reaction of a mixture of lithium salt (e.g. CH 3 COOLi$2H 2 O) and manganese oxides at around 750 C in air for many hours.…”
Section: Introductionmentioning
confidence: 99%
“…The high temperature could contribute to achieving highly crystalline spinel LiMn 2 O 4 , but it suffers from a problem by causing an oxygen deciency, which would lead to faster capacity fading during cycling. [3][4][5] In recent years, many other techniques have been reported in a large number of publications, such as hydrothermal and sol-gel methods, 2 the Pechni method, 6 spray drying, 7 microemulsion 8 and microwave hydrothermal techniques, 9 and controlled crystallization. 10 Spinel LiMn 2 O 4 , as a most promising substitute for LiCoO 2 in lithium ion battery cathode materials, [11][12][13] is attracting more and more attention from the public.…”
Section: Introductionmentioning
confidence: 99%
“…1 Granulation methods have a great effect on the particle size, morphology, and structure of materials, and the physical properties of materials are different when synthesized using different methodologies, even if the same starting materials are used. [2][3][4][5][6] Therefore, investigating a synthetic methodology through a detailed characterization of the products is essential for the discovery of new nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Several obstacles regarding the characterization of these types of materials were encountered and our paper has focus on identifying and alleviating these. [32][33][34][35] One particular concern is accurate phase analysis with powder X-ray diffraction (PXRD) in the presence of strong fluorescence (high background). It is shown that seemingly minor impurity contents can be deceptive, and that proper Rietveld modelling and multi-method analysis are necessary to obtain a correct material characterization.…”
Section: Introductionmentioning
confidence: 99%